Revisão de escopo sobre instrumentos de avaliação utilizados em Terapia Assistida por Cães - Bruno, Caroline Cristina (2024)
Animal-Assisted Therapy (AAT) is a type of Animal-Assisted Intervention (AAI) that consists of the intentional incorporation of an animal species in a therapeutic intervention according to previously defined objectives. The dog is one of the animals most frequently incorporated into AAT. There is literature that indicates the need for reliable measures to evaluate the effectiveness and benefits of this type of therapy. The study by Wilson and Netting (2012) was about the status of the development of assessment tools/instruments in the field of Human-Animal Interactions (HAI), with AAT falling within this field, but this field is not limited to AAI, nor this type of therapy. This study agreed with 140 evaluation tools/instruments, of which only 6 were specific for evaluating the effectiveness of some type of AAI. Of these 6, 4 were used in AAT, one in Animal Assisted Activity (AAA) and one in Animal Assisted Education (AAE), with the dog being the animal incorporated in 5 of the studies and the horse in one. Wilson and Netting (2012) conclude that based on the data found, it is not possible to carry out a meta-analysis on the current state of tools/instruments in the field of HAI and indicate the need for new reviews on the tools/instruments used, focusing on the purpose of their use . In this direction, we carried out a review of tools/instruments used in some type of AAI, specifically in AAT, a series of academic relevance contributing to the advancement and deepening of knowledge about reliable measures for evaluating the effectiveness and benefits of such type of therapy. Objectives: a) identify, characterize and evaluate the levels of evidence of studies on canine-assisted therapy that used evaluation tools/instruments that measure the effects of such therapy, b) identify and describe the evaluation tools/instruments. Methodology: scoping review in the National Library of Medicine's (PubMed), Elsevier's, Scielo and Google Scholar databases in the period from 2009 to 2023. Two searches were carried out, using the Boolean search strategy, with different descriptors, in the first search adopted - if “animal assisted intervention” AND/OR “animal assisted therapy”, in the second search we used “bonding” AND/OR “human-pet” (the same descriptors as Wilson and Netting (2012). The Rayyan platform was used to data organization. Data analysis was firstly quantitative, with the sum of the publications found and the final sample, with the findings expressed in a flowchart, graphs and tables. Secondly, the analysis was qualitative, involving the reading of all publications in the data. integrates and extracts information that answers the investigative questions. In the first search, 401 publications were found, after removing 14 duplicates. In the second search, 546 studies were found, after removing 33 duplicates. After reading the titles and abstracts, 397 publications from the first search and 545 publications from the second search were excluded, as they did not meet the inclusion criteria. However, the only publication from the second was a duplicate of a publication found in the first. Thus, the final sample consisted of 4 publications. Results: The sample was composed of publications by Silva and Osório (2018), Ávila Álvarez et al. (2020), Walden et al. (2020) and Moreira et al. (2016), and in all of them, canine-assisted therapy was carried out in children aged between 30 months and 12 years. In the study by Silva and Osório (2018), which evaluated the impressions of children undergoing outpatient cancer treatment about the Canine Assisted Therapy (CAT) program in which they participated, this assessment took place using an instrument created by the authors, consisting of five questions and not validated. In the study by Ávila-Álvarez et al. (2020) evaluated the effects of CAT in the area of social participation and changes that occur in children with Autism Spectrum Disorder (ASD), the evaluation took place through the questionnaire created by Richeson and McCullough (2002) composed of nine items, with questions on the frequency of child-dog interaction, which was previously validated by the authors who created it. The study by Walden et al. (2020) evaluated the impact of TAC on hospitalized children using a questionnaire with 5 questions, created by Wu et al. (2002), not yet validated. The study by Moreira et al. (2016) interviewed ten guardians and six nurses who were present in the oncological treatment process of children and adolescents who underwent TAC.